Societal Analysis of Shipyard Industry Development in Batupute Village, Soppeng Riaja District, Barru Regency - Nur Alif; Sakaria; Sultan (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
Industrial development is often embraced as a pathway to economic growth and improved living standards. However, contemporary development practices increasingly exhibit a tendency to overlook social, cultural, and environmental dimensions, resulting in an imbalanced development paradigm. This study aims to analyze community perspectives on the development of the shipbuilding industry in Batupute Village, Soppeng Riaja District, Barru Regency, using a societal approach. A qualitative research design was employed, with data collected through in-depth interviews using a snowball sampling technique to capture diverse perspectives from local residents. The analysis is grounded in the societal framework proposed by Paulus Wirutomo, which emphasizes the interconnection of structural, cultural, and processual dimensions in development. The findings indicate that the implementation of industrial development in the study area has not fully aligned with an ideal societal development model. Structurally, there are emerging inequalities and shifts in local economic patterns. Culturally, traditional values and community cohesion are experiencing gradual erosion. Processually, limited community participation and weak social integration mechanisms further exacerbate these issues. The lack of synchronization among these three dimensions reflects a broader disintegration within the development process. In conclusion, the development of the shipbuilding industry has yet to achieve a balanced integration of societal principles. These results underscore the importance of adopting more inclusive, participatory, and environmentally conscious development strategies to ensure that economic progress does not come at the expense of social and cultural sustainability